A Multiple-Input Strategy to Efficient Integrated Photonic Reservoir Computing - Katumba, Andrew; Freiberger, Matthias; Bienstman, Peter; Dambre, Joni (Cognitive Computation, 2017)
Photonic reservoir computing has evolved into a viable contender for the next generation of analog computing platforms as industry looks beyond standard transistor-based computing architectures. Integrated photonics reservoir computing, particularly on the Silicon-on-Insulator platform, presents a CMOS-compatible, wide-bandwidth, parallel platform for implementation of optical reservoirs. A number of demonstrations of the applicability of this platform for processing optical telecommunications signals have been made in the recent past. In this work, we take it a stage further by performing an architectural search for designs that yield the best performance while maintaining power efficiency.
Keywords: Reservoir Computing; Integrated Pho- tonics; Photonic Reservoir Computing; Reservoir Architectures